Analisis Faktor-Faktor Yang Mempengaruhi Minat Berwirausaha Pada Siswa SMK di Kabupaten Bekasi Jawa Barat - Hanggono Arie Prabowo (Jurnal Ilmiah Wahana Pendidikan, 2023)
Indonesia will experience a demographic bonus in 2030 of 297 million people. As many as 64% of the population will be of productive age or as many as 190 million people will be included in the workforce. This is the capital for Indonesia to create reliable personnel who have an interest in entrepreneurship. Entrepreneurial interest is an important factor in increasing the number of young entrepreneurs. Respondents were students of 2 SMKs located in Bekasi district, totaling 70 students. Data collection was taken through filling in boxes and interviews and documentation. The data is processed with the help of SPSS 21. The data is tested by reliability and collinearity tests. The results showed that the family environment, self-confidence, and creativity had an influence on the interest in entrepreneurship among vocational students in Bekasi district.